Les rituels dans la classe de Claire : d'une pédagogie inspirée de TEACCH à celle inspirée du Floor Time : quels changements ? - Delphine Odier-Guedj (Nantes Université, 2015)
In this paper, I will discuss the ritual as "a bodily movement with a beginning, an end and a clear direction. It therefore assigns a given position to participants. Body movements during the ritual provoke emotions that subsequently cause a change in ritual (Wulf, 2003: 65). The purpose of this article is to question the double orientation in rituals, that is to "create stability" and "set in motion", through one teacher's experience in working in a specialized class with students with Autism syndrome.